EFEKTIVITAS PELAKSANAAN MEDIASI SEBAGAI ALTERNATIF PENYELESAIAN SENGKETA PERSELISIHAN HUBUNGAN INDUSTRIAL - Adhi Pramudia, I Gusti Ngurah; A. Martana, Nyoman; Ari Krisnawati, I Gusti Ayu Agung (Kertha Wicara : Journal Ilmu Hukum; Vol. 01, No. 04, September 2013)
This paper entitled Effectiveness of the Implementation of Mediation as anAlternative Dispute Resolution of Industrial Relations Disputes, where the purpose ofthis paper is to determine the extent to which the effectiveness of mediation as analternative dispute resolution of industrial relations disputes. With settlement throughmediation, the parties do not have to dispute in court. This research uses empiricallegal research, with data coming from the Department of Labor and Transmigration ofBali. This paper will explain the mediation process and the effectiveness of mediation inthe settlement of industrial relations disputes and also explains the factors driving andinhibiting factors effectiveness of mediation in the settlement of industrial disputes.
Keywords: Mediation, Dispute Resolution, Industrial Relations